2012
DOI: 10.1186/1550-2783-9-s1-p28
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation and the quality of life of retired football players

Abstract: Studies suggest that playing professional football can impact the health of the athlete and concerns are raised that they may experience negative health consequences that may affect their quality of life when they retire. The purpose of this exploratory investigation is to determine the effects of dietary supplementation on the quality of life of retired football players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent preliminary investigations have suggested that nonpharmacological interventions may benefit contact sport athletes. Studies of professional football players report statistically significant improvements in neurocognitive function for up to 6 months with dietary supplementation (eg, omega‐3 fatty acids) . Additional research is needed to determine whether or not reported improvements were maintained in the long term .…”
Section: Ctementioning
confidence: 99%
“…Recent preliminary investigations have suggested that nonpharmacological interventions may benefit contact sport athletes. Studies of professional football players report statistically significant improvements in neurocognitive function for up to 6 months with dietary supplementation (eg, omega‐3 fatty acids) . Additional research is needed to determine whether or not reported improvements were maintained in the long term .…”
Section: Ctementioning
confidence: 99%